Dampak Keluarga Broken Home Terhadap Anak - Ariyanto, Komang (Jayapangus Press, 2023)
This study aims to describe the impact of broken home families on children. This study uses qualitative methods with various data collection techniques through interviews, observation, and literature studies. The results of the study show that: (1) the impact of behavioral problems on children who come from broken home families has good behavior and bad behavior due to their family background. (2) the impact on children due to broken home families can affect child development, behavior patterns, child psychology, as well as changes in sensitivity. (3) the occurrence of broken homes in the form of divorce due to economic problems, because the head of the household is unable to meet the needs of the family, and due to acts of verbal violence between spouses. (4) the solution for children due to broken home families is to always think positively, do positive things by focusing on dreams and goals, instilling motivation within oneself, and finding a place to share (vent).